2018
DOI: 10.1021/acs.biochem.7b00919
|View full text |Cite
|
Sign up to set email alerts
|

Structures of the Peptidoglycan N-Acetylglucosamine Deacetylase Bc1974 and Its Complexes with Zinc Metalloenzyme Inhibitors

Abstract: The cell wall peptidoglycan is recognized as a primary target of the innate immune system, and usually its disintegration results in bacterial lysis. Bacillus cereus, a close relative of the highly virulent Bacillus anthracis, contains 10 polysaccharide deacetylases. Among these, the peptidoglycan N-acetylglucosamine deacetylase Bc1974 is the highest homologue to the Bacillus anthracis Ba1977 that is required for full virulence and is involved in resistance to the host's lysozyme. These metalloenzymes belong t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 39 publications
1
17
0
3
Order By: Relevance
“…Acetate is one of the products of the deacetylation reaction, but its presence in the crystal structure of Ba0331 is most likely ascribable to impurities in the PEG crystallization medium (Blair et al, 2005). Similarly, in the previously reported homologous structures of Ba0330 (Arnaouteli et al, 2015) and Bc1974 (Giastas et al, 2018), which were determined at high resolution, acetate was also found bound to the zinc ion despite its absence from the initial constituents of the crystallization mixture. The near-octahedral coordination scheme of zinc is completed by a water molecule (Figs.…”
Section: The Conserved Zinc-binding Triad and The Nodb Homology Domainsupporting
confidence: 73%
See 4 more Smart Citations
“…Acetate is one of the products of the deacetylation reaction, but its presence in the crystal structure of Ba0331 is most likely ascribable to impurities in the PEG crystallization medium (Blair et al, 2005). Similarly, in the previously reported homologous structures of Ba0330 (Arnaouteli et al, 2015) and Bc1974 (Giastas et al, 2018), which were determined at high resolution, acetate was also found bound to the zinc ion despite its absence from the initial constituents of the crystallization mixture. The near-octahedral coordination scheme of zinc is completed by a water molecule (Figs.…”
Section: The Conserved Zinc-binding Triad and The Nodb Homology Domainsupporting
confidence: 73%
“…Specifically, MT1 and MT2 are involved in the immediate coordination of the active-site metal, MT3 and MT4 are located opposite to each other confining the binding site, while MT5 delimits the lower part of the binding groove (Arnaouteli et al, 2015;Giastas et al, 2018). In the catalytic groove (Figs.…”
Section: The Conserved Zinc-binding Triad and The Nodb Homology Domainmentioning
confidence: 99%
See 3 more Smart Citations